Adherence to Mediterranean diet, physical activity level, and severity of periodontitis: Results from a university‐based cross‐sectional study. Issue 8 (25th February 2022) - Marruganti, Crystal; Traversi, Jacopo; Gaeta, Carlo; Ferrari Cagidiaco, Edoardo; Parrini, Stefano; Discepoli, Nicola; Grandini, Simone
Abstract: Background: The aim of this study was to evaluate the association between adherence to Mediterranean diet (MD) and physical activity (PA) level with the periodontal status of a University‐based cohort of individuals. Methods: A total of 235 individuals were included in the study. MD adherence and PA level were registered through validated questionnaires, together with a full periodontal examination. Crude and adjusted odds ratios (ORs) [95% confidence interval] were calculated to evaluate the association between MD adherence, PA level, and periodontitis severity. A final logistic multivariate regression model was built to evaluate the impact of the combination between low MD adherence and low PA level on the prevalence of Stage III/IV periodontitis. Results: The adjusted ORs for Stage III/IV periodontitis were 1.65 [0.84 to 3.28; P = 0.42] for low PA and 5.63 [3.21 to 9.84; P = 0.00] for low MD adherence. The final logistic multivariate regression model resulted in OR = 10.23 [4.01, 26.09; P = 0.00] of having Stage III/IV periodontitis in individuals with low MD adherence and low PA. Conclusions: Individuals conducting a lifestyle characterized by the combination of low MD adherence and lack of regular exercise had 10 times the odds to have severe forms of periodontitis.